O domínio territorial republicano manifestado na multiexpressividade da Comissão Rondon - Teodoro, Cristiane Aparecida Zambolin (2017)
This paper aims at demonstrating the contributions that the Strategic Telegraph Commission of Amazonas - CLTEMTA (1907 to 1915) made to the processes of appropriation and territorial domination exercised by the Republican State during the First Republic or Old Republic (1889 - 1930), corresponding to the areas north-west of Brazil, in short Mato Grosso, in the so-called "empty hinterland". There fore, it is based on the idea that CLTEMTA has a multi-expressive character, since it consisted of multiple scientific, social, economic, protective, cultural, ideological or territorial purposes, factors that were determinant for the process of legitimation in a society that was in the process of composition.